Pengaruh Kredibilitas Idol Group JKT48 Sebagai Celebrity Endorser Produk Erigo Terhadap Niat Beli Konsumen - Bani Ady Ramadhan; Istiharini; Theresia Gunawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the impact of the credibility of the idol group JKT48 as a celebrity endorser on consumer purchase intentions for Erigo products. In the rapidly growing digital marketing era, the use of celebrity endorsers has become a key strategy in influencing consumer purchase decisions. JKT48, as an idol group with significant influence, was chosen to test how much their credibility affects consumer purchase intentions for Erigo, a local fashion brand that is rapidly growing. This study employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to respondents who are fans of JKT48 and users of Erigo products. The variables tested include three dimensions of credibility: trustworthiness, expertise, and attractiveness, and their influence on consumer purchase intentions. The results of the study indicate that the credibility of JKT48 as a celebrity endorser influences consumer perception of Erigo products, which in turn affects consumer purchase intentions. The dimensions of trustworthiness, expertise, and attractiveness all prove to have a significant impact on consumers' positive perceptions and purchase intentions for Erigo products. These results confirm that the credibility of JKT48 as a celebrity endorser can strengthen consumer views on the quality and value of Erigo products, which leads to increased purchase intentions.